In vitro Antibacterial and Antifungal Activity of Borreria articularis (Bangladesh Journal of Microbiology, 2010)
Petroleum ether extract, chloroform extract, ethyl acetate extract, ethyl alcohol extract and a pure compound 6-methyl-5-cyclodecen-1-ol obtained from aerial parts of Borreria articularis were studied for their antimicrobial activities against eleven human pathogenic bacteria and four human pathogenic fungi using disc diffusion and poisoned food method respectively. Ethyl acetate extract, ethanol extracts and the pure compound 6-methyl-5-cyclodecen-1-ol exhibited good antibacterial and antifungal activity against all the pathogens tested herein. The ethanol extract and 6-methyl-5-cyclodecen-1-ol exhibited the largest zone of inhibition (20 mm) at a concentration of 2,000 ìg/disc against Escheichia coli and Vibrio cholerae respectively. In case of fungi, the crude extract of ethanol and the pure compound exhibited the highest inhibition 53.5 and 52.0% of fungal radial mycelial growth (with 100 ìg/ml medium) against Aspergillus ustus and A. ochraceus respectively. The minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC) and minimum fungicidal concentration (MFC) of the pure compound 6-methyl-5-cyclodecen-1-ol were determined by broth macrodilution method. The lowest MIC (500 μg/ml) and MBC (1,000 μg/ml) were determined against V. cholerae. However, for fungi, the lowest MIC (750 μg/ml) and MFC (1,500 μg/ml) were recorded against A. ochraceus. The results suggest that active antimicrobial agent(s) present in the extracts of B. articularis may have potential for the treatment of bacterial and fungal infections. Keywords: Antimicrobial activity; Borreria articularis; Crude extracts; 6-Methyl-5 cyclodecen-1-olDOI: http://dx.doi.org/10.3329/bjm.v25i2.4869 Bangladesh J Microbiol, Volume 25, Number 2, December 2008, pp 95-98